PECULIARITIES OF METABOLIC REACTiONS IN INDIGENOUS AND MIGRANT POPULATIONS OF THE NORTH AND SIBERIA - M. A. Darenskaya (Acta Biomedica Scientifica)
The review presents current researches of peculiarities of hormonal status, lipid and carbohydrate metabolism of indigenous and migrant populations of the North and Siberia. It is known that extreme climatic and geographical conditions are more demanding to the metabolic status. Features of protein-lipid and carbohydrate metabolism in the North and Siberia are determined by biologically built adaptive type and are connected with adherence of indigenous population to traditional lifestyle and "Asian" type of food. However in the last two decades the decline of quality of health of ethnic groups is registered due to a number of social reasons. Changing lifestyles and food ration causes the development of dysadaptive reactions in the whole organism and the subsequent development of diseases. Numerous studies on metabolic changes in migrant population depending on the length of stay in the northern territories, latitude, seasons, age and gender are conducted.